A Family-Oriented Decision-Making Model for Human Research in Mainland China. Issue 4 (3rd July 2015) - Rui, Deng
Abstract: This essay argues that individual-oriented informed consent is inadequate to protect human research subjects in mainland China. The practice of family-oriented decision-making is better suited to guide moral research conduct. The family's role in medical decision-making originates from the mutual benevolence that exists among family members, and is in accordance with family harmony, which is the aim of Confucian society. I argue that the practice of informed consent for medical research on human subjects ought to remain family-oriented in mainland China. This essay explores the main features of this model of informed consent and demonstrates the proper authority of the family. The family's participation in decision-making as a whole does not negate or deny the importance of the individual who is the subject of the choice, but rather acts more fully to protect research subjects.